PENGARUH PENERAPAN PENDEKATAN LINGKUNGAN TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Sugianti, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to determine how much influence the application of environmental approaches toward IPA’s learning outcomes on grade V SDN 01 Rasau Jaya. Research methods that used is experimental method and the form was a quasi experimental design, with Nonequivalent Control Group Design. The subjects were 58 students consisting of 26 men and 32 women. Data collection tool used in the form of multiple choice test of 30 questions. The results showed the average of experimental class learning is 77,48 and at the control class learning is 66,90. Based on T test obtained tarithmetic of 4.3719 and ttable with significance α = 5% (with dk = 29 + 29 - 2 = 54) is 1.6736, which means tarithmetic (4.3719) > ttable (1.6736) Then Ha acceptable. That’s means there is influence the application of environmental approaches toward IPA’s learning outcomes on grade V SDN 01 Rasau Jaya. From the calculation of effect size (ES), obtained ES is 1,14 (high criteria). Thus concluded that the application of environmental approaches provide high influence toward IPA’s learning outcomes on grade V SDN 01 Rasau Jaya. Keywords : Environmental Approaches, Learning Outcomes